2019
DOI: 10.1002/acr2.1022
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapist‐Led Triage at a Rheumatology‐Based Musculoskeletal Assessment Clinic: an 18‐Month Service Evaluation of Activity and Outcomes

Abstract: ObjectivePhysiotherapist‐led musculoskeletal triage clinics are an effective and efficient means of managing patients presenting with musculoskeletal disorders in primary and secondary care. Data regarding the activity and outcomes of physiotherapist‐led triage in hospital‐based outpatient rheumatology clinics are scarce. Thus, the aim of this study was to undertake a service evaluation of activity and outcomes of a physiotherapist‐led rheumatology‐based Musculoskeletal Assessment Clinic (MAC). The primary obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Of the 63 articles screened for full text, a total of 28 articles were included in the review. The 28 included studies were published from 1999 to 2022 [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The following study designs were identified: 10 RCTs, 9 prospective longitudinal cohort studies, 4 case control studies, 3 retrospective observational studies, and 2 prospective observational studies [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 63 articles screened for full text, a total of 28 articles were included in the review. The 28 included studies were published from 1999 to 2022 [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. The following study designs were identified: 10 RCTs, 9 prospective longitudinal cohort studies, 4 case control studies, 3 retrospective observational studies, and 2 prospective observational studies [ 9 , 16 , 17 , 18 , 19 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…A referral rule with high specificity can overcome inappropriate referrals to an outpatient rheumatology clinic. This specificity results in a lower individual and societal burden of musculoskeletal symptoms and a reduction of waiting times for rheumatology outpatient clinics (21). When looking for which referral rule is most effective in keeping inappropriate referrals from expensive outpatient care, CARE seems most accurate of the 2 existing rules.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies on MSKD care in primary care or the ED have had follow-up periods ranging from six to 24 months (e.g. [26,[39][40][41][42]). Thus, the Markov model will cover a 24-month period.…”
Section: Study Design and Costing Approachesmentioning
confidence: 99%